Culturally Responsive Teaching: An Approach to Cultivate Students' Global Diversity Character - Annisa Nurramadhani; Yuyun Elizabeth Patras; Resyi Abdul Ghani; Yoshikazu Tatemoto; Rista Chamelia Anggraeni; Arin Fajar Sisworo (FKIP UNIVERSITAS PAKUAN, 2025)
This research aims to investigate students’ global diveristy character in elementary school with culturally responsive teaching (CRT) appraoch. This research method used in this study is descriptive quallitative with 26 students who in fifith grader of elementary schools. They are coming from different ethnic groups (Sundaness, Javaness, Minangkabau, Sunda-Java, Sunda-Batak). CRT is implemented in mathematical learning with Problem based learning model. Mathematical subject is integrated with cultural and local wisdom. Global diversity character is taken by global diversity character questionnaire with 20 statements. The results shows that the communication and interaction between culture aspect gain the highest results, while the lowest is recognising and appreciating culture. And there is the influence of students’ ethnic background to the global diversity character in the learning. It could be concluded that CRT approach could cultivate students’ global diversity character skills in mathematics learning.